UPAYA PENINGKATAN KINERJA PEGAWAI PEMADAM KEBAKARAN DALAM MENANGANI KEBAKARAN DI WILAYAH KABUPATEN WONOSOBO - Sobar Sobar; Mudasetia Hamid (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study aims to analyze the factors influencing firefighter performance and identify efforts to improve this performance in Wonosobo Regency. Employee performance is a crucial factor in determining the effectiveness of public services, particularly in firefighting, which requires high levels of preparedness, responsiveness, and professionalism. The research method used a qualitative descriptive approach with a case study of the Firefighting and Rescue Division of the Wonosobo Regency Regional Disaster Management Agency (BPBD). Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The research results indicate that employee performance is suboptimal due to limited human resources (HR) numbers and competencies, a lack of training and certification, and inadequate facilities and infrastructure. Efforts to improve this are being made through the recruitment of certified employees, regular training and simulations, increased cross-agency collaboration, the procurement of new equipment, and the establishment of fire stations in each sub-district. With the support of competent human resources, adequate facilities, and good coordination, fire service performance is expected to become more effective and professional.